Phytosociological surveys: tools for weed science? - Concenço,G. (2013)
In simple terms, a phytosociological survey is a group of ecological evaluation methods whose aim is to provide a comprehensive overview of both the composition and distribution of plant species in a given plant community. To understand the applicability of phytosociological surveys for weed science, as well as their validity, their ecological basis should be understood and the most suitable ones need to be chosen, because cultivated fields present a relatively distinct group of selecting factors when compared to natural plant communities. For weed science, the following sequence of steps is proposed as the most suitable: (1) overall infestation; (2) phytosociological tables/graphs; (3) intra-characterization by diversity; (4) inter-characterization and grouping by cluster analysis. A summary of methods is established in order to assist Weed Science researchers through their steps into the realm of phytosociology.